2020
DOI: 10.3390/su12041501
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Data for Urban Climate Change Adaptation: Reviewing Applications, Opportunities and Key Challenges

Abstract: Climate change places cities at increasing risk and poses a serious challenge for adaptation. As a response, novel sources of data combined with data-driven logics and advanced spatial modelling techniques have the potential for transformative change in the role of information in urban planning. However, little practical guidance exists on the potential opportunities offered by mobile phone data for enhancing adaptive capacities in urban areas. Building upon a review of spatial studies mobilizing mobile phone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Another interesting approach to Climate Change and adaptation was collecting and analyzing mobile phone data for the analysis of urban population activities and mobility patterns at high spatial and temporal resolutions. Technologies such as mobile phone data are a main asset for addressing climate-related risk within cities, better addressing the vulnerability of urban communities and managing climate risks in a continuous manner, thereby overcoming the limitations of static planning approaches based on population estimations from census data [55].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting approach to Climate Change and adaptation was collecting and analyzing mobile phone data for the analysis of urban population activities and mobility patterns at high spatial and temporal resolutions. Technologies such as mobile phone data are a main asset for addressing climate-related risk within cities, better addressing the vulnerability of urban communities and managing climate risks in a continuous manner, thereby overcoming the limitations of static planning approaches based on population estimations from census data [55].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous [16,20,21,36] and current studies [10,[26][27][28][29] have shown the validity and benefits of mobility studies based on CDRs. Although event-based (i.e., data are only available when using the MNOs' services) and with coarse location (i.e., antennas that handled the service), CDRs are a real marker of human presence.…”
Section: Related Workmentioning
confidence: 95%
“…Indeed, multi-dimensional human mobility analyses would provide more insights into people's mobility behavior by attribute values (e.g., gender, origin, age-ranges). For instance, local authorities and/or organizations could take advantage of such knowledge to identify strategies to propose better decision-making solutions to society, e.g., the spread of diseases, urban planning, natural disasters, and so on [10,20,21,26,28,29,36].…”
Section: Purpose and Contributionsmentioning
confidence: 99%
See 2 more Smart Citations